Downregulation of neuronal vasoactive intestinal polypeptide in Parkinson's disease and chronic constipation. Issue 5 (27th November 2016) - Giancola, F.; Torresan, F.; Repossi, R.; Bianco, F.; Latorre, R.; Ioannou, A.; Guarino, M.; Volta, U.; Clavenzani, P.; Mazzoni, M.; Chiocchetti, R.; Bazzoli, F.; et al.
Abstract: Background: Chronic constipation (CC) is a common and severe gastrointestinal complaint in Parkinson's disease (PD), but its pathogenesis remains poorly understood. This study evaluated functionally distinct submucosal neurons in relation to colonic motility and anorectal function in PD patients with constipation (PD/CC) vs both CC and controls. Methods: Twenty‐nine PD/CC and 10 Rome III‐defined CC patients were enrolled. Twenty asymptomatic age‐sex matched subjects served as controls. Colonic transit time measurement and conventional anorectal manometry were evaluated in PD/CC and CC patients. Colonoscopy was performed in all three groups. Colonic submucosal whole mounts from PD/CC, CC, and controls were processed for immunohistochemistry with antibodies for vasoactive intestinal polypeptide (VIP) and peripheral choline acetyltransferase, markers for functionally distinct submucosal neurons. The mRNA expression of VIP and its receptors were also assessed. Key Results: Four subgroups of PD/CC patients were identified: delayed colonic transit plus altered anorectal manometry (65%); delayed colonic transit (13%); altered manometric pattern (13%); and no transit and manometric impairment (9%). There were no differences in the number of neurons/ganglion between PD/CC vs CC or vs controls. A reduced number of submucosal neurons containing VIP immunoreactivity was found in PD/CC vs controls ( P< .05). VIP, VIPR1, and VIPR2 mRNA expression was significantly reduced in PD/CC vs CC and controls ( P <.05). Conclusions and Inferences: Colonic motor and rectal sensory functions are impaired in most PD/CC patients. These abnormalities are associated with a decreased VIP expression in submucosal neurons. Both sensory‐motor abnormalities and neurally mediated motor and secretory mechanisms are likely to contribute to PD/CC pathophysiology. Abstract : Chronic constipation is usually a severe gastrointestinal dysfunction in patients with Parkinson's disease, but its pathogenesis remains poorly understood. This study evaluated functionally distinct submucosal neurons in relation to colonic motility and anorectal function in PD patients with constipation (PD/CC) vs both CC and controls. Colonic motor and rectal sensory functions resulted impaired in most parkinsonian constipated patients. Compared with controls, they display a decreased number of submucosal secretomotor neurons containing VIP immunoreactivity accompanied by a reduced mRNA expression of VIP and VIP receptors.